Assessing employment in Malta - Aaron G. Grech (Central Bank of Malta, 2003)
In this paper, the total number of employed and the full-time equivalent employment in Malta are estimated for the last three decades. These series give a new picture of the historical development of employment and productivity in Malta. The estimated full-time equivalent time series, in spite of its limitations, is a first step on the way towards a comprehensive statistical measure of labour input in Malta.
Keywords: 330